The gene expression of CTRP12 but not CTRP13 is upregulated in both visceral and subcutaneous adipose tissue of obese subjects. Issue 4 (July 2019) - Omidifar, Abolfazl; Toolabi, Karamollah; Rahimipour, Ali; Emamgholipour, Solaleh; Shanaki, Mehrnoosh
Abstract: Obesity is a well-known chronic low-grade inflammation condition characterized by dysregulated adipokine secretion and function. Both CTRP12 and CTRP13 are adipokines that influence glucose and lipid metabolism. We aimed to investigate CTRP12, CTRP13, and inflammatory gene expressions in subcutaneous adipose tissue (SAT) and visceral adipose tissue (VAT) from obese women who underwent bariatric surgery in comparison with the normal weight women. This case-control study included 20 obese [body mass index (BMI) > 35–40 kg/m 2 ] candidates for bariatric surgery and 20 normal-weight women (BMI <25 kg/m 2 ) as control group, who underwent elective surgeries. Real-time PCR was used to evaluate mRNA expression levels of CTRP12, CTRP13, and inflammatory genes in SAT and VAT from both groups. We observed significantly higher mRNA expression of CTRP12 in SAT (p = 0.048) and VAT (p = 0.046) from obese patients compared to the controls. There was significantly greater expression of IL-6 and MCP-1 inflammatory genes in SAT (p = 0.013 and p = 0.005 respectively) and VAT (p = 0.000 and p = 0.001 respectively) of obese patients compared to the control group. IL-1β (p = 0.015) and TNF-α (p = 0.014) expressions significantly increased in VAT from obese patients compared to the control group. Spearman correlation analysis showed that CTRP12 expression significantly correlated with obesity indices. Our findings showed that CTRP12 significantly increased in both VAT and SAT of obese group. More importantly, we observed a positive correlation between CTRP12 with inflammatory parameters. These results indicated that CTRP12 might be part of an intricate network for glucose metabolism and obesity-related inflammation processes.